On Stackelberg Leader with Min-Max Followers to Solve Fuzzy Continuous Static Games. (11th April 2022) - Khalifa, Hamiden Abd El Wahed; Pamucar, Dragan; Alburaikan, Alhanouf; Afifi, W. A.
Abstract : This study attempts to introduce continuous static games with fuzzy parameters. Piecewise quadratic fuzzy numbers (PQFNs) are used to represent the fuzzy parameters. The close interval approximation of the PQFNs, which is one of the most accurate approximations, is applied. To overcome the problem, Stackelberg leaders with min-max follower's solutions are examined. The given solution is accompanied by a parametric analysis. An algorithm for identifying the first-kind stability set is presented. Finally, to demonstrate and clarify the method's steps, a numerical example is given